In Vitro Anthelmintic Activity of Orthosiphon aristatus (Blume) Miq Leaves Against Haemonchus contortus - Indria Augustina; Debora Jesika; Pransiska Elma; Trinovita Elsa; Francisca Diana Alexandra; Arif Rahman Jabal (Jurnal Ilmu Pertanian Indonesia, 2024)
Haemonchosis is an infection caused by the Haemonchus contortus worm, a blood-sucking gastrointestinal parasite that can also infect humans. Orthosiphon aristatus (Blume) Miq leaves have been shown to have anthelmintic activity due to the presence of saponins, flavonoids, and tannins. This study aimed to determine the anthelmintic activity of ethanol extract of Orthosiphon aristatus (Blume) Miq leaves against H. contortus. The infective H. contortus larvae were divided into six treatment groups: a 0.5% ethanol extract concentration group, a 1% ethanol extract concentration group, a 2% ethanol extract concentration group, a 4% ethanol extract concentration group, a positive control group (+), and a negative control group (-), each with four replicates. The study was conducted in six hours, with observations made at the 1st, 2nd, 4th, and 6th hours. The results showed that the death of the larvae increased with higher ethanol extract concentrations and longer exposure to the ethanol extract of Orthosiphon aristatus (Blume) Miq leaves. The time of death for infective H. contortus larvae given the ethanol extract of Orthosiphon aristatus (Blume) Miq leaves was at the 4th hour, and the effective dose of the ethanol extract as an anthelmintic was at the concentration of 0.5%. Keywords: Anthelmintic, Haemonchus contortus, Orthosiphon aristatus